Pergeseran Diskursus Akidah Islamiyah di Era Digital: Analisis Literatur Sistematis terhadap Publikasi Dekade Terakhir - Rahman, Mahadi (Lembaga Anotero Scientific Pekanbaru, 2025)
This study conducted a Systematic Literature Review (SLR) to analyze the shifting discourse of Aqidah Islamiyah (Islamic creed) in the digital era from 2015–2025. The findings reveal a paradigmatic transformation in Islamic theological discourse—from text-centered to media-centered orientation—where digital influencers and online religious authorities have begun to redefine traditional epistemological structures. While digitalization has democratized religious knowledge and broadened access to Islamic learning, it also contributes to the rise of theological distortion and pseudo-religious narratives. This review identifies four dominant themes in current research: the reconfiguration of religious authority, theological distortion, digital religious literacy, and epistemological reconstruction in cyberspace. The study concludes that the digital era presents both opportunities and challenges for maintaining theological authenticity, requiring Islamic scholars and educators to integrate classical theology with digital communication literacy. Strengthening digital religious literacy and developing ethical frameworks for online da’wah are essential for preserving the integrity of Islamic creed in the age of artificial intelligence.